Geophysical exploration of disseminated and stockwork deposits associated with plutonic intrusive rock: a case study on the eastern flank of colombia’s western cordillera (2012)
Disseminated deposits are low-grade, large tonnage deposits which are mainly mined for gold, copper, molybdenum and tin. These deposits are normally associated with intermediate to acid plutonic intrusive rocks and all are characterized by intense, extensive hydrothermal alteration of host rocks. Disseminated deposit exploration in the tropics suffers from difficult geological mapping due to dense vegetation, lack of rock outcrops and extensive but variable saprolytic weathering. Geophysical exploration of these deposits normally includes magnetic, induced polarization and gamma ray spectrometry surveys. The largest RTP total magnetic field anomaly highs are usually associated with diorite porphyry intrusive bodies. Diorites are usually less magnetic than basaltic rocks; thus when magnetic anomaly highs are related to intrusions they can be explained by basic metals’ intensive mineralization (including magnetite) associated with porphyry intrusions. Magnetic anomaly gradients regularly help delineate local discontinuities which can be interpreted as local faults and joints that can be mineralized. Gamma ray spectrometry is useful for determining anomalous potassium, uranium and thorium concentration as it can map alteration halos and linear discontinuities. Statistical analysis of the data also can determine the intermediate intrusive / extrusive nature of porphyry intrusions. Gamma ray spectrometry can help to determine elemental potassium concentration, regardless of the associated potassium mineral species, thereby enabling alteration mapping in a geological setting related to volcanic-associated massive sulphide base metal and gold deposits. An induced polarization survey is useful in outlining disseminated sulphide distribution in porphyry deposits related to chargeability anomaly highs. The results of the Quinchía project’s geophysical exploration program are discussed.